2019
DOI: 10.1186/s13018-019-1299-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginsenoside Rb1 on spinal cord ischemia-reperfusion injury in rats

Abstract: Background The aim of this study was to evaluate the effects of different doses of ginsenoside Rb1 (GRb1) pretreatment on spinal cord ischemia-reperfusion (SCII) in rats and explore the potential mechanisms about the expression of survivin protein after the intervention. Methods A total of 90 healthy adult Sprague-Dawley (SD) rats were randomly divided into six groups: sham-operated ( n = 15), SCII model ( n = 15), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In this study, we demonstrated that the administration of GRb1 could alleviate SCI, as evidenced by the increase of BBB score, reduction of TUNEL positive cell percentage, and amelioration of histopathologic lesions, which was in line with previous studies (Huang et al, 2015; Zhao et al, 2018). For instance, Ye et al (2019) showed that the introduction of GRb1 could improve rat locomotor function, reduce malondialdehyde content, and increase superoxide dismutase level in serum and spinal cord tissues, ameliorate histopathologic abnormality of the spinal cord, facilitate survivin expression in spinal cord tissues, and inhibit neuronal cell apoptosis in SCI rats. Huang et al (2015) demonstrated that GRb1 enhanced rat locomotor function, relieved neuronal injury, and inhibited spinal cord cell apoptosis in SCI rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we demonstrated that the administration of GRb1 could alleviate SCI, as evidenced by the increase of BBB score, reduction of TUNEL positive cell percentage, and amelioration of histopathologic lesions, which was in line with previous studies (Huang et al, 2015; Zhao et al, 2018). For instance, Ye et al (2019) showed that the introduction of GRb1 could improve rat locomotor function, reduce malondialdehyde content, and increase superoxide dismutase level in serum and spinal cord tissues, ameliorate histopathologic abnormality of the spinal cord, facilitate survivin expression in spinal cord tissues, and inhibit neuronal cell apoptosis in SCI rats. Huang et al (2015) demonstrated that GRb1 enhanced rat locomotor function, relieved neuronal injury, and inhibited spinal cord cell apoptosis in SCI rats.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord segments (about 20 mm) containing injured sites were harvested for subsequent experiments. The concentration of GRb1 in SCI animal model mainly referred to a prior study (Ye et al, 2019), which pointed out that GRb1 at the concentration of 40 mg/kg has the best therapeutic effect on SCI in the rat model. In animal and cell model, GRb1 was dissolved in 0.9% physiological saline to a stock concentration of 5 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…energy metabolism (Nanao-Hamai et al, 2019;Ye et al, 2019;Zhou et al, 2019). Rb1 can protect cardiomyocytes from hypoxia/ischemia injury in vitro, and its protective mechanism primarily involves inhibiting the mitochondrial pathway of apoptosis (Yan et al, 2014).…”
Section: Ginsenoside Rb1mentioning
confidence: 99%
“…GRb1, ginsenoside Rb1; I/R, indicates ischemia and reperfusion. (Yang et al, 2008;Liu et al, 2013;Ye et al, 2019), acute renal injury-protective Sun et al, 2012;Chen et al, 2019), cardiovascularprotective Xia et al, 2011;Zheng et al, 2017;Li et al, 2020), lung injury-protective (Wang et al, 2013;Chen et al, 2014;Jiang et al, 2015;Li et al, 2015), and antiaging (Dong et al, 2017;Zhou et al, 2019a) effects, in many in vitro and in vivo models.…”
Section: Introductionmentioning
confidence: 99%